a)
The formula for integrating by parts is
∫udvdxdx=uv−∫vdudxdx.
We choose u=5x−6 and dvdx=cos(3x+7).
So dudx=5 and v=13sin(3x+7).
Hence,
∫(5x−6)cos(3x+7)dx=uv−∫vdudxdx=(5x−6)sin(3x+7)−5∫sin(3x+7)dx3=5x−63sin(3x+7)+59cos(3x+7)+C
b)
For this part we choose u=(5x−6)2 and dvdx=sin(3x+7).
So dudx=10(5x−6) and v=−13cos(3x+7).
Hence,
I=∫(5x−6)2e3xdx=uv−∫vdudxdx=−(5x−6)2cos(3x+7)+∫10(5x−6)cos(3x+7)dx3=−(5x−6)2cos(3x+7)+10∫(5x−6)cos(3x+7)dx3…(∗)
But in Part a we have aready worked out ∫(5x−6)cos(3x+7)dx=5x−63sin(3x+7)+59cos(3x+7)
So on substituting this in equation (*) we find:
I=−(5x−6)2cos(3x+7)+10(5x−63sin(3x+7)+59cos(3x+7))3+C=−(5x−6)23cos(3x+7)+10(5x−6)9sin(3x+7)+5027cos(3x+7)+C